Peningkatan Penyesuaian Diri di Sekolah Melalui Layanan Konseling Kelompok pada Siswa - Astri Nindhy Hutami; Muswardi Rosra; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The purpose of the study was to determine the improvement of students' self-adjustment abilities using Group Counseling with Client Centred technique for grade VII students of State JHS 1 Central Tulang Bawang academic year of 2018/2019. The study applied experimental method of the Pretest-Posttest One-Group design. The research subjects consisted of 6 students with low self-adjustment abilities. The data collection techniques were done using scale of adjustment and structured observation. The results showed that students' self-adjustment abilities could be improved using Group Counseling Services with client-centred technique. The results of data analysis showed that the pre test and post test t-calc = -2.207 t table 0.05 = 1.645. The hypothesis of Ha is accepted, meaning that the adjustment ability of grade VII students of State JHS 1 Central Tulang Bawang academic year of 2018/2019 could be improved using the Group Counseling Service with client-centred technique. The conclusion revealed that there is an increase in students' self-adjustment ability before the treatment of Group Counseling Service with client-centred technique and after being given treatment of Group Counseling Service with client-centred technique for grade VII students of State JHS 1 Central Tulang Bawang academic year of 2018/2019. Tujuan penelitian untuk mengetahui peningkatan kemampuan penyesuaian diri siswa menggunakan Konseling Kelompok dangan teknik Client Centred pada siswa kelas VII SMP Negeri 1 Tulang Bawang Tengah Tahun Pelajaran 2018/2019. Metode penelitian adalah metode eksperimen desain One-Group Pretest-Posttest. Subjek penelitian sebanyak 6 orang siswa dengan kemampuan penyesuaian diri rendah. Teknik pengumpulan data menggunakan skala penyesuaian diri dan observasi terstruktur. Hasil penelitian menunjukkan bahwa kemampuan penyesuaian diri siswa dapat ditingkatkan menggunakan Layanan Konseling Kelompok dengan teknik client centred. Terbukti dari hasil analisis data pre test dan post test thitung = -2,207 ttabel0,05 = 1,645. Maka Ha diterima, artinya kemampuan penyesuaian diri siswa kelas VII SMP Negeri 1 Tulang Bawang Tengah Tahun Pelajaran 2018/2019 dapat ditingkatkan dengan menggunakan Layanan Konseling Kelompok dengan teknik client centred. Kesimpulannyaadalah terdapat peningkatan kemampuan penyesuaian dirisiswa sebelum diberi Layanan Konseling Kelompok dengan teknik client centred dan setelah diberi Layanan Konseling Kelompok dengan teknik client centred pada siswa kelas VII SMP Negeri 1 Tulang Bawang Tengah Tahun Pelajaran 2018/2019.Kata kunci: konseling kelompok, penyesuaian diri, teknik client centred